Tindak Pidana Korupsi dan Upaya Penindakan oleh Aparat Penegak Hukum - Bambang Sasmita Adi Putra; Didi Syaputra (PT PUSTAKA CENDEKIA GROUP, 2026)
Corruption in Indonesia is no longer a new problem in legal matters for the country because the problem of corruption has existed for thousands of years, both in developed countries and in developing countries, including Indonesia. The problem of the development of corruption in Indonesia is now so severe and has become an extraordinary problem because it has infected and spread to all levels of society. Corruption crimes in the past were regulated in the Criminal Code due to the dynamics that developed in society, then these regulations underwent changes that were more specific or Lex Specialis which were then regulated for the first time regulated in Law No. 31 of 1999 in conjunction with amendments to Law Number 20 of 2001 concerning the Eradication of Corruption Crimes (PTPK Law). In its course, corruption activities are carried out by the highest power holders who have positions, which positions are mostly the result of winning elections in a party. In the PTPK Act. it is stated that people who commit corruption must compensate the state for losses, due to the economic and social impact of an area it causes on state finances. In its journey, the addition of prison sentences for serious corruptors, of course, has a deterrent effect on perpetrators of corruption, with which it is hoped that acts of corruption can be reduced.